Gallium nitride sintered body and method for producing same
The production of a gallium nitride-based sintered body with controlled oxygen and impurity levels addresses the challenges of film instability and cost in existing methods, enabling high-quality, large-scale production of sputtering targets for diverse LED colors.
Patent Information
- Application Number
- JP2019184361
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-11-14
- Filing Date
- 2019-10-07
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2039-10-07
AI Technical Summary
Existing methods for producing gallium nitride thin films face challenges such as instability due to metallic gallium melting, high costs of sputtering targets, poor homogeneity, and inclusion of oxygen and impurities, which affect film quality and productivity, especially when scaling up to larger substrates and incorporating elements like aluminum and indium for different LED colors.
A gallium nitride-based sintered body with controlled oxygen content, high density, and specific impurity levels is produced using a hot press method with precise thermal expansion matching and vacuum conditions, enabling large-scale production of sputtering targets without tungsten intermediates.
The solution results in high-strength, crack-free gallium nitride sintered bodies suitable for large-area sputtering targets, improving film quality and productivity while reducing costs and enabling production of green and red LEDs.
Smart Images

Figure 0007600520000005 
Figure 0007600520000006 
Figure 0007600520000001
Abstract
Description
[Technical field]
[0001] Gallium nitride has attracted attention as a raw material for the light-emitting layer of blue light-emitting diodes (LEDs) and blue laser diodes (LDs), and in recent years has been used in various applications such as white LEDs and blue LDs in the form of thin films or substrates, and is also attracting attention as a material for power devices and other applications in the future. Currently, gallium nitride thin films are generally manufactured by the metalorganic chemical vapor deposition (MOCVD) method. The MOCVD method is a method in which the vapor of the raw material is contained in a carrier gas and transported to the substrate surface, where the raw material is decomposed by reaction with the heated substrate, thereby growing crystals.
[0002] Another method for producing thin films other than MOCVD is the sputtering method, which physically bombards a target placed at the cathode with positive ions such as Ar ions, releasing the material that makes up the target with the collision energy, and depositing a film with approximately the same composition as the target material on a substrate placed opposite it. There are two types of sputtering: direct current sputtering (DC sputtering) and radio frequency sputtering (RF sputtering).
[0003] Until now, a metal gallium target has been used as a method for forming a gallium nitride thin film by sputtering (see, for example, Patent Document 1). However, when using a metal gallium target, since the melting point of metal gallium is about 29.8°C, it melts during sputtering, making it difficult to obtain a gallium nitride film with highly stabilized properties such as crystallinity and transparency. To prevent this, a method has been proposed in which an expensive cooling device is installed and the film is formed at a low power, but this method has the problem of reducing productivity and easily increasing the intake of oxygen into the film.
[0004] In addition, a high-density gallium nitride sintered body has also been proposed (see, for example, Patent Document 2), but according to the examples, it becomes dense under very high pressure conditions of 58 Kbar (5.8 GPa), and the equipment for applying such pressure is very expensive, so it is not possible to produce a large sintered body. Therefore, the sputtering target itself used in the sputtering method is very expensive, and it is difficult to make it large, so there is a problem that the film tends to be poor in homogeneity.
[0005] As a method for reducing the amount of oxygen contained, a method has been proposed in which the amount of oxygen is reduced by subjecting an oxygen-containing gallium nitride sintered body to a nitriding treatment (see, for example, Patent Document 3). However, there is a problem in that reducing the amount of oxygen beyond a certain level can cause cracks in the sintered body.
[0006] In addition, when using a direct current sputtering method, the resistivity of the sputtering target is required to be low. As a method for this purpose, a method has been proposed in which the resistivity of the sputtering target is reduced by infiltrating metallic gallium into the gallium nitride molded product (see, for example, Patent Document 4). However, this method reduces the resistance, but there is a problem that metallic gallium precipitates during bonding or sputtering, reacting with a solder material such as indium, causing the gallium nitride molded product to peel off, and discharging cannot be performed stably. As a countermeasure, a method has been proposed in which the precipitation of metallic gallium is suppressed by lining with a thin film of tungsten (see, for example, Patent Document 5), but there are problems such as an increase in the number of target preparation steps, which makes it complicated, and the need to use a special material, such as expensive tungsten material.
[0007] Moreover, in recent years, research has been progressing on forming gallium nitride films on large silicon substrates, and even larger sputtering targets will be required in the future, but such targets do not currently exist.
[0008] Furthermore, gallium nitride LEDs are being sought that are not only blue, but also green and red, and to achieve this, they need to contain aluminum and indium, but no sputtering targets capable of producing such colors have been available to date. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] Japanese Patent Application Publication No. 11-172424 [Patent Document 2] JP 2005-508822 A [Patent Document 3] JP 2012-144424 A [Patent Document 4] JP 2014-159368 A [Patent Document 5] JP 2014-91851 A Summary of the Invention [Problem to be solved by the invention]
[0010] An object of the present invention is to provide a gallium nitride-based sintered body containing a Group 13 element such as aluminum, which has high strength and is free of cracks, and a sputtering target using the same. [Means for solving the problem]
[0011] In view of this background, the present inventors have conducted extensive research and have found that by treating gallium nitride powder with a low oxygen content with a hot press mold having an appropriate holding time and a thermal expansion coefficient suited to gallium nitride sintering, it is possible to produce a high-density, large-sized gallium nitride sintered body with a low oxygen content, and have completed the present invention.
[0012] That is, the aspects of the present invention are as follows. (1) A gallium nitride sintered body having a content of one or more Group 13 elements selected from the group consisting of boron, aluminum, and indium of 0.001 atm % or more and 25 atm % or less, and an oxygen content of 1 atm % or less. (2) The gallium nitride sintered body according to (1), characterized in that the oxygen content is less than 0.3 atm %. (3) A gallium nitride sintered body according to (1) or (2), characterized in that the total amount of impurities of the elements Si, Ge, Sn, Pb, Be, Mg, Ca, Sr, Ba, Zn, and Cd is less than 10 wtppm. (4) A gallium nitride sintered body according to any one of (1) to (3), characterized in that the total amount of impurities of Mg and Si is less than 5 wtppm. (5) A gallium nitride sintered body according to any one of (1) to (4), characterized in that the amount of Si impurity is less than 1 wtppm. (6) Density is 3.0 g / cm 3 More than 5.4g / cm 3 The gallium nitride sintered body according to any one of (1) to (5) above, characterized in that: (7) A gallium nitride sintered body according to any one of (1) to (6), characterized in that, among the X-ray diffraction peaks of the sintered body, the maximum value of the peak attributable to metal gallium is 10% or less of the maximum value of the gallium nitride peaks. (8) A gallium nitride sintered body according to any one of (1) to (7), characterized in that the average grain size of the sintered body is 1 μm or more and 150 μm or less. (9) A method for producing a gallium nitride-based sintered body by a hot pressing method according to any one of (1) to (8), characterized in that gallium nitride powder having an oxygen content of 1 atm% or less and one or more Group 13 elements selected from the group consisting of boron, aluminum and indium are used as raw materials, and the difference between the linear thermal expansion coefficient in a direction perpendicular to the pressing direction of the hot pressing mold and the linear expansion coefficient of the raw material is within 15%. (10) The method for producing a gallium nitride sintered body according to (9), wherein the hot press mold is used to obtain a disk, and the sleeve is divided into three or more parts. (11) A sputtering target comprising the gallium nitride sintered body according to any one of (1) to (8). (12) A sputtering target according to (11), characterized in that no layer containing tungsten exists between the target member and the bonding layer. (13) A method for producing a gallium nitride-based thin film, comprising using the sputtering target according to (11) or (12).
[0013] The gallium nitride sintered body of the present invention is characterized in that the total content of one or more group 13 elements selected from the group consisting of B, Al, and In is 0.001 atm% to 25 atm%, preferably 0.01 atm% to 25 atm%, and more preferably 0.1 atm% to 25 atm%. By obtaining such a gallium nitride sintered body containing B, Al, and In, it becomes possible to form a sputtering target and use the formed gallium nitride thin film as a thin film for green or red LEDs or a thin film for power devices.
[0014] The gallium nitride sintered body of the present invention has an area of 150 cm 2 Preferably 175cm or more. 2 More preferably, it is equal to or greater than 200 cm. 2 By obtaining a large-area gallium nitride sintered body, it becomes possible to increase the size of the substrate on which a film can be formed.
[0015] The oxygen content is also characterized by being 1 atm% or less, preferably 0.5 atm% or less, more preferably less than 0.3 atm%, even more preferably 0.2 atm% or less, and even more preferably 0.1 atm% or less. By reducing the oxygen content in the gallium nitride sintered body, when it is used as a sputtering target, it is possible to reduce the inclusion of oxygen as an impurity during film formation and obtain a film with higher crystallinity.
[0016] Here, atm% is synonymous with at%, and is expressed as the ratio of the number of atoms of a specific element to the number of atoms of all elements contained. For example, in gallium nitride containing oxygen, when gallium, nitrogen, and oxygen are each contained in wt%, the oxygen content (atm%) is Oxygen content (atm%) = (Oxygen content (wt%) / Oxygen atomic weight) / ((Gallium content (wt%) / Gallium atomic weight) + (Nitrogen content (wt%) / Nitrogen atomic weight) + (Oxygen content (wt%) / Oxygen atomic weight)) It becomes.
[0017] In order to enable the gallium nitride sintered body of the present invention to be controlled to a p-type or n-type semiconductor, it is preferable that the gallium nitride sintered body contain the total impurity amount of the elements Si, Ge, Sn, Pb, Be, Mg, Ca, Sr, Ba, Zn, and Cd in the gallium nitride sintered body of less than 10 wtppm, more preferably 5 wtppm or less, and particularly preferably 3 wtppm or less.
[0018] Among the impurities, Mg and Si, which have a high activation rate, are preferably contained in a total amount of 5 wtppm or less, more preferably 2 wtppm or less, and particularly preferably 1 wtppm.Furthermore, the amount of Si impurity is preferably 1 wtppm or less.
[0019] The gallium nitride sintered body of the present invention preferably has a flexural strength of 50 MPa or more, more preferably 60 MPa or more, and even more preferably 70 MPa or more. With such strength, even a sintered body with a large area can be produced without cracking, and even when used as a sputtering target, the sintered body can withstand the stress applied to it in the bonding process.
[0020] The gallium nitride sintered body of the present invention has a density of 3.0 g / cm 3 More than 5.4g / cm 3 It is preferable that the concentration is 3.5 g / cm or less, and more preferably 3.5 g / cm 3 More than 5.4g / cm 3 Less than 4.0 g / cm3 More than 5.4g / cm 3 The density of the gallium nitride sintered body mentioned here refers to the density including the open pores. Such a gallium nitride sintered body can be used as a sputtering target.
[0021] The gallium nitride sintered body of the present invention preferably has an average particle size (D50) of 1 μm or more and 150 μm or less, more preferably 5 μm or more and 100 μm or less, and particularly preferably 9 μm or more and 80 μm or less. By setting the particle size to such an extent, it is possible to obtain a gallium nitride sintered body having a smaller amount of oxygen and high strength. The average particle size (D50) here refers to the 50% particle size in terms of the area of the primary particles observed with a scanning electron microscope or the like.
[0022] Also, it is preferable that there is little metallic gallium in the sintered body. In particular, the maximum value of the peak due to metallic gallium in the X-ray diffraction peak is preferably 10% or less of the maximum value of the gallium nitride peak, more preferably 5% or less, and even more preferably 1% or less. If metallic gallium is present in the sintered body, it will be alloyed with one or more group 13 elements selected from the group consisting of B, Al, and In contained therein, and will become liquid due to a decrease in melting point, and the sintered body will not be able to retain its shape or will crack. Also, when used as a sputtering target, Ga-(B,Al,In) alloy will precipitate during sputtering, making stable film formation difficult.
[0023] Next, a method for producing a gallium nitride sintered body according to the present invention will be described.
[0024] In order to obtain a large, low-oxygen sintered body without causing cracks in the gallium nitride sintered body, it is necessary to sinter the gallium nitride sintered body as little as possible without applying stress to it.
[0025] That is, the method for producing a gallium nitride sintered body of the present invention is a method for producing a gallium nitride sintered body by a hot pressing method, and is characterized in that gallium nitride powder having an oxygen content of 1 atm% or less and powder of one or more Group 13 elements selected from the group consisting of boron, aluminum and indium are used as raw materials, and the difference between the linear thermal expansion coefficient in the direction perpendicular to the pressure direction of the hot press mold and the linear expansion coefficient of the raw material is within 15%.
[0026] The method for producing a gallium nitride sintered body of the present invention will now be described in more detail.
[0027] First, the oxygen content of the gallium nitride powder used as the raw material must be 1 atm% or less. More preferably, it is less than 0.5 atm%, more preferably, it is less than 0.3 atm%, more preferably, it is 0.2 atm% or less, and even more preferably, it is 0.1 atm% or less. In order to reduce oxygen, it is necessary to suppress oxidation of the surface, so it is preferable that the specific surface area of the powder is small, and more preferably, it is 0.01 m. 2 / g or more 1.5m 2 / g or less, more preferably 0.01m 2 / g or more 0.8m 2 / g. 2 When the specific surface area is smaller than 1 / g, the crystal particles are too large, so the adhesive force between the particles is weak, making it difficult to maintain the shape during final firing. Furthermore, the sinterability generally decreases, making firing difficult.
[0028] In order to obtain a gallium nitride sintered body with sufficient strength as a sputtering target, the bulk density of the raw material gallium nitride powder must be 1.0 g / cm 3 More than 3.0g / cm 3 It is preferably less than 1.4 g / cm 3 More than 3.0g / cm 3 The light bulk density is a value calculated by filling a container with powder without applying any load such as vibration, and dividing the volume of the powder by the volume of the container. 3If the light bulk density is too high, the strength of the granules constituting the powder becomes too high, and the granules remain uncrushed during molding and sintering, resulting in a significant decrease in the strength of the gallium nitride sintered body.
[0029] In addition, the average particle size (D50) of the gallium nitride powder used as the raw material is preferably 1 μm or more and 150 μm or less. It is more preferably 5 μm or more and 100 μm or less, and even more preferably 9 μm or more and 80 μm or less. By using such powder, it is possible to manufacture a gallium nitride sintered body that is both high strength and low oxygen. In particular, in the case of gallium nitride, the sintering start temperature and the decomposition temperature are close to each other, the sintering temperature range is narrow, and the grains do not grow significantly during sintering, so the distribution of the primary particles before sintering has a large effect on the gallium nitride sintered body. The particle size of the primary particles refers to the diameter of the smallest unit particle observed by SEM, and the average particle size refers to the value at 50% grain size after measuring at least 100 particles by the diameter method. The particles for which the average particle size is measured here are gallium nitride particles. In the case of molded products using powders within this range, the particle size is larger than conventional powders and the adhesive strength is weaker. Therefore, if there are open pores large enough to allow immersion, the bonding strength between the particles is relatively weak. Therefore, when Ga is immersed, cracks will occur due to the stress generated during immersion and the difference in thermal expansion coefficient caused by heating and sputtering.
[0030] In order to obtain high crystallinity of the sputtered film and to change the semiconductor properties by adding elements, it is preferable to use gallium nitride powder that contains as few impurities as possible as the raw material. However, to obtain p-type and n-type semiconductors, the gallium nitride powder preferably contains less than 10wtppm of the total impurity elements Si, Ge, Sn, Pb, Be, Mg, Ca, Sr, Ba, Zn, and Cd, more preferably 5wtppm or less, and particularly preferably 3wtppm or less.
[0031] Among the impurities, Mg and Si, which have a high activation rate, are preferably contained in a total amount of 5 wtppm or less, more preferably 2 wtppm or less, and particularly preferably 1 wtppm.Furthermore, the amount of Si impurity is preferably 1 wtppm or less.
[0032] Similarly, it is preferable to use boron, aluminum, and indium that contain as few impurities as possible. The purity of the metal impurities is preferably 99 wt% or more, and more preferably 99.9 wt% or more.
[0033] The form of boron, aluminum, and indium to be contained is not particularly limited, and since it is preferable that oxygen is contained as little as possible and other metal elements are not contained, metallic boron, boron nitride, metallic aluminum, aluminum nitride, metallic indium, and indium nitride are preferable. Metallic aluminum, aluminum nitride, metallic indium, and indium nitride are more preferable. The amount of oxygen contained in the raw material is preferably 3 atm% or less, more preferably 1.5 atm% or less, and even more preferably 1 atm% or less. By doing so, it is possible to obtain a gallium nitride sintered body with a reduced amount of oxygen.
[0034] The sintering method used is the hot press method, which sinters powder by applying pressure and heat, and uniaxial pressure is applied while heating to assist diffusion during sintering, making it possible to sinter materials that have a low diffusion coefficient and are difficult to sinter.
[0035] The difference in the linear thermal expansion coefficient of the hot press mold in the direction perpendicular to the pressure direction from the thermal expansion coefficient of the raw material to be put in is preferably within 15%, more preferably within 10%, and even more preferably within 5%. More preferably, it is +1% or less and -5% or more with respect to the thermal expansion coefficient of the raw material. The linear thermal expansion coefficient of the hot press mold here is the value for the mold in FIG. 1. When producing a gallium nitride sintered body, it is 5.0×10 -6 / K or more 7.0×10 -6 / K or less, and more preferably 5.0×10 -6 / K or more 6.0×10 -6 / K or less. By using materials with a thermal expansion coefficient in this range, the linear thermal expansion coefficient becomes close to that of gallium nitride, making it possible to reduce the stress applied when enlarging the size. In the case of small sizes, sintering was possible even if the linear thermal expansion coefficient was different because the dimensional difference was small, but fine cracks were included, which was a cause of reduced strength. 2 If the temperature exceeds this range, the difference in dimensions due to the difference in thermal expansion will become large, causing stress during firing and resulting in cracks. -6 / K or less, when pressure sintering is performed at a specified temperature, the shrinkage of the hot press mold is smaller than that of the gallium nitride sintered body when the temperature is decreased, resulting in large tensile stress and cracking of the gallium nitride sintered body. -6 3. At temperatures of 1000 to 2000 K or more, the hot press mold shrinks more than the gallium nitride sintered body when the temperature is lowered, generating external compressive stress, which in turn causes cracks in the gallium nitride sintered body, resulting in a decrease in strength and breakage.
[0036] An example of a hot press mold is shown in Fig. 1, and it is preferable that the materials of the die, upper punch, lower punch, and sleeve in this figure are the same. By using the same materials, the volume change during heating becomes similar, making it possible to reduce stress during thermal expansion and contraction.
[0037] The firing temperature is 1060° C. or higher and lower than 1200° C. A temperature of 1060° C. or higher is necessary to promote the sintering of gallium nitride, and a temperature of less than 1200° C. is required to suppress the decomposition of gallium nitride into nitrogen and metallic gallium to a certain amount. In addition, the pressure during firing is preferably 30 MPa or higher and 100 MPa or lower, and more preferably 40 MPa or higher and 90 MPa or lower, in order to improve the density of the gallium nitride-based sintered body.
[0038] The firing temperature depends on the particle size of the powder used; the larger the particle size, the higher the temperature that can be applied.
[0039] The holding time during sintering is preferably 15 minutes or more and less than 1 hour. If it is less than 15 minutes, the density will increase due to partial decomposition of gallium, but the adhesion between particles will not progress. If it is sintered for longer than 1 hour, the decomposition will progress and alloy with the contained boron, aluminum, and indium, lowering the melting point, making it impossible to maintain strength even if the density increases. By sintering within this range, it is possible to suppress decomposition while progressing sintering, and it is possible to obtain a gallium nitride sintered body with higher strength than ever before.
[0040] The hot press is performed in a vacuum atmosphere. The degree of vacuum at the start of heating is 10 Pa or less, and 1×10 -1 Pa or less is preferable, and 5×10 -2 Pa is more preferable, 1×10 -2 It is particularly preferable that the pressure is equal to or less than Pa. This makes it possible to reduce oxygen and oxygen elements such as water that are mixed in from the atmosphere, and to suppress oxidation during firing.
[0041] In addition, when sintering in a vacuum, the decomposition of the gallium nitride powder gradually progresses from around 1060°C, but by sintering in a vacuum, some of the metallic gallium produced by the decomposition is discharged to the outside from the gallium nitride sintered body together with nitrogen, which is the decomposition gas. For this reason, it is preferable that the clearance between the die and the upper punch in the hot press mold is 0.2 mm or more. Alternatively, it is preferable to use a low-density material such as carbon felt between the powder and the upper and lower punches.
[0042] The hot press mold preferably includes a split sleeve. More preferably, the sleeve is split into 3 or more parts, and even more preferably, 4 or more parts. The maximum number of parts is preferably 6 or less. Splitting the sleeve in this way makes it easier to remove the gallium nitride sintered body, and makes it possible to prevent cracking and chipping.
[0043] In order to reduce the amount of oxygen adsorbed to the hot press mold, it is preferable to perform a pre-baking process before firing, which makes it possible to reduce the amount of moisture adsorbed to the hot press apparatus and mold before firing.
[0044] The obtained gallium nitride sintered body is preferably in a disk shape, since the disk shape allows thermal expansion and contraction to be uniform in the circumferential direction, making it possible to suppress the stress applied to the gallium nitride sintered body.
[0045] The obtained gallium nitride sintered body may be processed to a predetermined size depending on the application such as a sputtering target, etc. The processing method is not particularly limited, but a surface grinding method, a rotary grinding method, a cylindrical grinding method, or the like can be used.
[0046] The gallium nitride sintered body may be fixed (bonded) to a flat or cylindrical support with an adhesive such as a solder material as necessary to form a sputtering target. It is preferable that the sputtering target does not have a layer containing tungsten between the target member and the bonding layer. By not using an expensive metal tungsten target, costs can be reduced, and a tungsten film formation process is unnecessary, improving productivity.
[0047] In addition, in the sputtering target of the present invention, it is preferable to use a tin-based solder material, an indium-based solder material, or a zinc-based solder material as the bonding layer. Among these, indium solder is particularly preferable because it has high electrical conductivity and thermal conductivity, is soft, and is easily deformed.
[0048] In addition, the sputtering target of the present invention is preferably made of a metal such as Cu, SUS or Ti, since it has high thermal conductivity and high strength as a support. As for the shape of the support, it is preferable to use a flat support for a flat molded product, and a cylindrical support for a cylindrical molded product.
[0049] Next, a method for producing the sputtering target of the present invention will be described.
[0050] The sputtering target of the present invention is manufactured by bonding a gallium nitride sintered body to a support via a bonding layer. For the bonding layer, a tin-based solder material, an indium-based solder material, a zinc-based solder material, etc. can be used. When an indium-based solder material is used, a layer for improving wettability may be formed between the gallium nitride sintered body and the solder material in order to improve the indium wettability to the gallium nitride sintered body. The material of the layer is preferably inexpensive and has high wettability to indium, for example, a nickel-based or chromium-based material. This layer is preferably formed uniformly over the entire interface with the solder material. There is no particular limitation on the method for forming such a barrier layer, and sputtering, vapor deposition, coating, etc. can be used. Effect of the Invention
[0051] The gallium nitride sintered body of the present invention is suitable for use as a sputtering target for thin films of LEDs of various colors. [Brief description of the drawings]
[0052] [Figure 1] Hot press mold used in the examples and comparative examples [Diagram 2] Four-part sleeve used in the example EXAMPLES
[0053] The present invention will be described below with reference to examples, but is not limited thereto. (Lightweight bulk density) The measurements were carried out using a powder tester PT-N type (manufactured by Hosokawa Micron). (Density of gallium nitride sintered body) The density of the gallium nitride sintered body was measured in accordance with the bulk density measurement method specified in JIS R1634. (oxygen content) The oxygen content was measured using an oxygen / nitrogen analyzer (manufactured by LECO). (Measurement of average particle size (D50)) The average particle size (D50) was measured by the diameter method in at least three fields of view from SEM observation images, and the 50% particle size was taken as the average particle size after measuring more than 100 particles. The measurement subjects were only gallium nitride particles in gallium nitride powder and gallium nitride sintered compacts. (flexural strength) The flexural strength of the sintered body was measured according to JIS R 1601 after machining to an appropriate size. (Impurity analysis) Impurities other than gas components were analyzed using GDMS (glow discharge mass spectrometry). (Method of confirming crystal phase and measuring intensity ratio) For normal measurements, a general powder X-ray diffractometer (Ultima III, manufactured by Rigaku Corporation) was used. The conditions for XRD measurements were as follows:
[0054] Radiation source: CuKα radiation (λ=0.15418nm) Measurement mode: 2θ / θ scan Measurement interval: 0.01° Divergence slit: 0.5deg Scattering slit: 0.5deg Receiving slit: 0.3mm Measurement time: 1.0 seconds Measurement range: 2θ=20°~80° XRD analysis software (product name: JADE7, manufactured by MID Co., Ltd.) was used for the identification analysis of the XRD patterns. The gallium nitride crystal phase was confirmed for the hexagonal crystal with reference to JCPDS No. 00-050-0792, and the ratio of the highest peaks was confirmed for metallic gallium with reference to, for example, JCPDS No. 00-005-0601. Peak intensity ratio (%) = maximum peak intensity of metallic gallium / maximum peak intensity of gallium nitride (Examples 1 to 6) Gallium nitride powder with elements added at the ratios shown in Table 1 was used in Example 1 (600 g), and in Examples 2 to 6 (120 g) and placed in a carbon mold with the thermal expansion coefficient of the die in Table 2, and then placed in a hot press. The degree of vacuum reached before the start of heating was the condition shown in Table 2, and sintering was started under the conditions shown in Table 2, the temperature was raised at 200°C / h, and finally increased to the temperature in Table 2, and the pressure conditions at that time were raised to the pressure shown in Table 2 when the maximum temperature was held, and hot press processing was performed with the temperature and pressure held for 2 hours. The temperature was lowered to about 50°C, the mold was removed, and the sintered body was collected. Table 3 shows the area, X-ray peak intensity ratio, density, oxygen content, flexural strength, and average particle size (D50) of the obtained gallium nitride sintered body.
[0055] The results of the impurity amounts in Example 1 are shown in Table 4.
[0056] (Comparative Examples 1 to 3) Using the gallium nitride powder shown in Table 1, hot pressing was performed under the same conditions as in Example 2, except that the conditions were those shown in Table 2. The results of the area, X-ray peak intensity ratio, density, oxygen content, flexural strength and average particle size (D50) of the obtained gallium nitride-based sintered body are shown in Table 3. In Comparative Example 1, no sintered body was obtained and the area could not be measured.
[0057] [Table 1]
[0058] [Table 2]
[0059] [Table 3]
[0060] [Table 4] [Explanation of symbols]
[0061] 1 Sleeve 2 Dice 3 Upper punch 4 Lower punch
Claims
1. The content of one or more Group 13 elements selected from the group consisting of boron, aluminum, and indium is 0.001 atm % or more and 25 atm % or less, the oxygen content is 1 atm % or less, and the density is 3.0 g / cm 3 5.4g / cm or more 3 and wherein the average grain size of the sintered body is 1 μm or more and 150 μm or less.
2. 2. The gallium nitride sintered body according to claim 1, characterized in that the oxygen content is less than 0.3 atm %.
3. 3. The gallium nitride sintered body according to claim 1, characterized in that the total amount of impurities of the elements Si, Ge, Sn, Pb, Be, Mg, Ca, Sr, Ba, Zn, and Cd is less than 10 wtppm.
4. 4. The gallium nitride sintered body according to claim 1, further comprising a total impurity content of Mg and Si of less than 5 wtppm.
5. 5. The gallium nitride sintered body according to claim 1, further comprising a silicon impurity content of less than 1 wtppm.
6. 6. A gallium nitride sintered body according to claim 1, wherein the maximum value of the peak attributable to metal gallium in the X-ray diffraction peaks of the sintered body is 10% or less of the maximum value of the gallium nitride peaks.
7. 7. The gallium nitride sintered body according to claim 1, wherein the flexural strength is 50 MPa or more.
8. 8. A method for producing a gallium nitride sintered body by hot pressing, comprising the steps of: using as raw materials a gallium nitride powder having an oxygen content of 1 atm % or less and a powder of one or more group 13 elements selected from the group consisting of boron, aluminum and indium; performing hot pressing in a vacuum atmosphere; and determining whether the difference between the linear thermal expansion coefficient in a direction perpendicular to the pressure direction of the hot press mold and the linear expansion coefficient of the raw material is within 15%.
9. 9. The method for producing a gallium nitride sintered body according to claim 8, characterized in that the hot press mold for obtaining a disk has a sleeve divided into three or more parts.
10. A sputtering target comprising the gallium nitride sintered body according to any one of claims 1 to 7.
11. 11. The sputtering target of claim 10, wherein there is no tungsten-containing layer between the target member and the bonding layer.
12. A method for producing a gallium nitride thin film, comprising using the sputtering target according to claim 10 or 11.
Citation Information
Patent Citations
Production of gallium compound
JP1999172424A
Method for manufacturing group iii nitride substrate and semiconductor device
JP2005012171A
Sintered polycrystalline gallium nitride and its production method
JP2005508822A
Gallium nitride sintered body or gallium nitride molded article, and method for producing them
JP2012144424A
Gallium nitride target and method of producing the same
JP2014091851A
